Dimensionless Analysis of Centrifugal Fan Characteristics: Experimental Evaluation at Three Rotational Speeds - Xu, Xinrui (International Journal of Mechanical and Electrical Engineering, 2025)
The aerodynamic performance of centrifugal fans has been studied due to their wide application in industrial and engineering fields such as ventilation, air circulation, and thermal management. This paper investigates the performance characteristics of a backward-curved blade centrifugal fan at approximately 1000, 2000, and 2700 rpm through experimental methods. The experimental apparatus comprised a calibrated nozzle, diffuser, universal dynamometer, slide valve, and digital pressure display for precise measurement of pressure rise, volumetric flow rate, electrical power, and efficiency. By progressively altering the slide valve opening, pressure-difference versus flow rate curves and efficiency versus flow rate curves were obtained. The results demonstrated typical centrifugal fan characteristics: pressure rise initially increased then decreased with rising volumetric flow rate, while efficiency peaked at medium-to-high flow rates. To validate hydrodynamic similarity, dimensionless parameters including flow coefficient, pressure difference coefficient, and power coefficient were calculated. Results demonstrate that the dimensionless pressure and power curves at different rotational speeds largely coincide, confirming the principle of dynamic similarity. However, significant deviations occur at low rotational speeds, primarily attributed to increased friction losses, flow separation, and slip effects. This study confirms the applicability of dynamic similarity in centrifugal fans and reveals the influence of Reynolds number and efficiency variations under low-speed conditions, providing a reference for fan design optimization and performance prediction.